Abdominal wall hydatid cyst in child - Hicham Ajdar; Khalid Khattala; Othmane Alaoui; Abdelhalim Mahmoudi; Youssef Bouabdallah (Elsevier, 2022)
The abdominal wall hydatid cyst is a rare entity. Very few cases are reported in the literature. The clinical presentation is not specific. Ultrasound can guide the diagnosis and the use of CT is often essential. We describe the case of a child who presented with a primary localization of the abdominal wall hydatid cyst, and who underwent surgical excision with good evolution.